Sixteen years changes in tree density and aboveground biomass of a logged and burned dipterocarp forest in East Kalimantan, Indonesia - TAKESHI TOMA; WARSUDI WARSUDI; YOKO OSONE; SUTEDJO SUTEDJO; TAMOTSU SATO; SUKARTININGSIH SUKARTININGSIH (Biodiversitas Journal of Biological Diversity, 2017)
Toma T, Warsudi, Osone Y, Sutedjo, Sato T, Sukartiningsih. 2017. Sixteen years changes in tree density and aboveground biomass of a logged and burned dipterocarp forest in East Kalimantan, Indonesia. Biodiversitas 18: 1159-1167. Changes in tree density and aboveground biomass (AGB) of a logged and burned lowland dipterocarp forest were monitored in Bukit Soeharto Research and Education Forest (BSREF) of Mulawarman University, East Kalimantan, Indonesia. A 9-ha plot was established in 1997 to investigate the effect of second felling and the subsequent recovery. Experimental felling was conducted in October 1997, and the plot was burned by uncontrolled fires between February and April 1998. Stem diameter of living trees (diameter at breast height ≥ 10 cm) in the plot was recorded annually. Allometric functions and the annual tree inventory were used to estimate changes in AGB. Tree density in the 9-ha plot was 429 trees ha−1 before the experimental felling.This decreased to 76 trees ha−1 in 2000 because of the felling and fires. Tree density increased to 515 trees ha−1 until 2008 and then decreased to 408 trees ha−1 in 2014. AGB of the 9-ha plot was 279 Mg ha−1 in 1997,which decreased to 96 Mg ha−1 in 2000 and then increased to 139 Mg ha−1 in 2014. After 16 years of the 1998 fires, in 2014, BSREF consists of a mosaic of forest stands that are dominated by either large late successional tree species or small pioneer trees. The former stands consisted of numerous late successional tree species that survived the felling and fires. The latter stands were dominated by a few pioneer species. In 2016, 16 years after the fire, these pioneer dominating stands are now undergoing a transitional stage from pioneer to late successional trees that grow longer and larger than the pioneer trees. Logged and burned forest stands may recover their AGB comparable to that of the original forest (≥400 Mg ha−1), if these stands are saved from further logging and fires in the longterm.